Teachers’ decision-making processes during situated teamwork - Julie Lysberg; Fredrik Rusk (Education Inquiry)
Structured teacher collaboration has considerable potential to support teachers’ professional learning. The current article focuses on what characterises teachers’ decision-making processes during teamwork. Video recordings of teacher team meetings form the empirical basis for the research. Interaction analysis is employed to analyse under what circumstances decisions are taken and to examine how teachers make use of conceptual resources (lived and formal concepts) in decision-making processes. For teams to accept proposals for decisions, they appear to need to be justified through pedagogical concepts; that is, when lived and formal concepts are linked. This study shows how the development of teachers’ pedagogical concepts during teamwork is a collective process. The teachers also re-conceptualise and re-shape the concepts to strengthen their relevance in the context of their future work.